(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
In this research, the deep drawing dies are designed by using finite element software to save time and facilitate the design process and FE Method is used to simulate the drawing process to select the best die design, also. A commercially available finite elements software (ANSYS 14.0 APDL) was used to perform the numerical simulation. With this regard, the effects of various parameters such as punch pressure, blank diameter, frictional and connection conditions and material flow were investigated. AA8011 used as blank material. Experiments done on 100 tonne deep drawing setup. 1.5 mm thickness sheet give best results. Finite elements results were compared with experimental results.